Facebook in pedagogy: Insights from preservice teachers - Mohd Zulfadli, Mat Husin; Zuraina, Ali; Nur Farah Asmaq, Abdul Rahim; Ali, Imanat; Mukhtar, Hafsa; Younus, Muhammad (Transnational Press London Ltd, 2024)
Many have used Facebook to stay connected with family, relatives, and friends. It is also used to share and exchange informat ion. Nevertheless, the platform can be used for teaching as well. The study, therefore, investigates its use among preservice teachers in terms of assisting them in their teaching. Also, the study attempts to identify how the platform enhances teaching. Finally, it identifies the factors that impede them from using the teaching platform. In terms of methodology, the study employed qualitative research, namely exploratory research design employing 36 teachers as the samples. The study's findings produced three (3) major themes and ten (10) sub-themes following the research questions formulated. The study implied that Facebook is a potential platform teacher can use, although some were reluctant to use it. Teachers who are in the latter group believe that Facebook is a distraction. Therefore, they rejected its use to prevent their students from deviating when the platform is used in learning.